2021
DOI: 10.3389/feduc.2021.722169
|View full text |Cite
|
Sign up to set email alerts
|

Who Participates in Content-Focused Teacher Professional Development? Evidence From a Large Scale Study

Abstract: This study investigates the relationship between teacher quality and teachers’ engagement in professional development (PD) activities using data on 229 German secondary school mathematics teachers. We assessed different aspects of teacher quality (e.g. professional knowledge, instructional quality) using a variety of measures, including standardised tests of teachers’ content knowledge, to determine what characteristics are associated with high participation in PD. The results show that teachers with higher sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
2
0
1
Order By: Relevance
“…The results of the study detailing professional development showed a good effect on PCK. For instance, professional development programs (Ekmekci et al, 2019;Hidayat & Setyawan, 2020;Maboya et al, 2022;Sarkim, 2020), content-focused professional development (Richter et al, 2021), model/ professional training/ teacher training/ collaboration programs (Gambini & Lenart, 2021;Jeschke et al, 2021;Kurt-Birel et al, 2020;Manderfeld & Siller, 2019;Saputra et al, 2019;Sunzuma & Maharaj, 2019;Tang, 2018;Yildiz & Akyuz, 2019;Yilmaz & Demir, 2021), seminar/ workshops/ in-service training (Ansah et al, 2020;Chang et al, 2020;Kurt-Birel et al, 2020;Moh' d et al, 2021), educational course/ pedagogy course (Lau, 2019;Lee et al, 2018), school based continuous professional development/ on-site professional training (lesson study) (Helmbold et al, 2021;Mhakure, 2019), structured interventions/ professional learning workshops (Hilton & Hilton, 2018), regular meetings (Taylan et al, 2022), microteaching course/ microteaching/ teaching practicums (Setyaningrum et al, 2018) and a two-week summer institute (Schoen et al, 2019) were implemented to enhance mathematics teachers' PCK level effectively. Notably, terms such as model, professional training, teacher training and collaboration program were frequently used to represent professional development in most of the studies.…”
Section: Professional Developmentmentioning
confidence: 99%
“…The results of the study detailing professional development showed a good effect on PCK. For instance, professional development programs (Ekmekci et al, 2019;Hidayat & Setyawan, 2020;Maboya et al, 2022;Sarkim, 2020), content-focused professional development (Richter et al, 2021), model/ professional training/ teacher training/ collaboration programs (Gambini & Lenart, 2021;Jeschke et al, 2021;Kurt-Birel et al, 2020;Manderfeld & Siller, 2019;Saputra et al, 2019;Sunzuma & Maharaj, 2019;Tang, 2018;Yildiz & Akyuz, 2019;Yilmaz & Demir, 2021), seminar/ workshops/ in-service training (Ansah et al, 2020;Chang et al, 2020;Kurt-Birel et al, 2020;Moh' d et al, 2021), educational course/ pedagogy course (Lau, 2019;Lee et al, 2018), school based continuous professional development/ on-site professional training (lesson study) (Helmbold et al, 2021;Mhakure, 2019), structured interventions/ professional learning workshops (Hilton & Hilton, 2018), regular meetings (Taylan et al, 2022), microteaching course/ microteaching/ teaching practicums (Setyaningrum et al, 2018) and a two-week summer institute (Schoen et al, 2019) were implemented to enhance mathematics teachers' PCK level effectively. Notably, terms such as model, professional training, teacher training and collaboration program were frequently used to represent professional development in most of the studies.…”
Section: Professional Developmentmentioning
confidence: 99%
“…In educational systems where teachers can choose to participate in PD (e.g., in Germany) and PD is not mandatory due to external circumstances (e.g., distance learning during COVID-19-related school closures), there is evidence of a catalytic rather than an educative function of PD (D. Richter, Kunter, Klusmann, Lüdtke, & Baumert, 2011, Richter, Engelbert, Weirich, & Anand Pant, 2013E. Richter, Kunter, Marx, & Richter, 2021).…”
Section: Will and Skills: Teachers' Motivation And Technology-related...mentioning
confidence: 99%
“…In Bezug auf die Berufserfahrung zeigen Studien einheitlich, dass Lehrkräfte mit mehr Berufserfahrung zum einen weniger Bereitschaft äußern, an Fortbildungen teilzunehmen (Hauk et al 2022), und zum anderen auch mit weniger Wahrscheinlichkeit an Fortbildungsangeboten teilnehmen (E. . Befunde zu geschlechtsspezifischen Unterschieden sind hingegen uneinheitlich (E. Richter et al , 2021. Männer scheinen nach Krille (2020) öfter an Veranstaltungen im Bereich des Einsatzes Digitaler Medien teilzunehmen.…”
Section: Faktoren Zur Erklärung Individueller Unterschiede In Den For...unclassified